'It was still all me': self-forgetful autobiography in Seamus Heaney's Death of a Naturalist. Issue 4 (21st April 2018) - Bauer, Mark
ABSTRACT: This article challenges the customary practice of reading Heaney's early work autobiographically by examining a tension that appears in Heaney's prose, which simultaneously champions lyric self-forgetfulness and the primacy of the self. This tension manifests itself through the exclusive use of the past tense in some of these early lyrics, a formal feature that destabilises self-reference by requiring very different tasks and perspectives from the 'I' who takes part in the poem's diegetic events and the 'I' who retells them. If these poems are indeed to be read as autobiography, this overt decentring of the 'I' demands a more capacious view of the genre. The result is what I term self-forgetful autobiography, which resituates the self in the poem's language and gestures rather than in a referential 'I' who can be equated with the poet.